Application of Milkfish Bone-Based Gelatin as an Alternative to Non-halal Gelatin - Setyabudi, Latif; Pambudi, Alfian Wisnu; Gunawan, Setiyo (Halal Research, 2024)
Collagen partially hydrolyzes to produce gelatin that functions as a gelling and non-gelling agent for various industries. Currently, Indonesia cannot produce its own gelatin, so to meet its needs, Indonesia imports 100%. However, many imported gelatins are still made from pork, so they need to be replaced to ensure that the gelatin is halal . This paper discusses the substitution of pork-based gelatin with milkfish bones. The general process for making gelatin from milkfish bones involves extracting, drying, demineralizing, degreasing, and determining the gelatin yield. Brackish water fish collagen, including milkfish, contains approximately 12–14 kDa parvalbumin, suggesting the potential for allergic reactions among consumers. Meanwhile, the critical point for halal gelatin extracted from milkfish bones is the origin of the milkfish bones and the use of citric acid as an extractor. Although there are still weaknesses, gelatin from milkfish can replace pork-based gelatin, and it can have a positive impact on the Indonesian economy by reducing gelatin imports.